Comparison of Time and Cost Efficiency: Conventional Scaffolding vs. Perth Construction Hire in Building Construction Projects (Case Study: Integrated Medical Education Building, Jenderal Soedirman University) - Lutfi Zukhruf Humaira; Siti Nurasiyah; Naufal Ariq Pratama (Portal: Jurnal Teknik Sipil, 2025)
The selection of scaffolding type is a crucial aspect in construction project execution, as it significantly affects time effectiveness and cost efficiency. This study aims to analyze the cost and time associated with the use of scaffolding and Perth Construction Hire (PCH) in the construction project of the IME Building at Jenderal Soedirman University (UNSOED), and to compare both methods in order to determine the most optimal alternative. The research employs a descriptive quantitative approach, conducted through observation and the collection of secondary data, including detailed engineering design (DED) drawings, Unit Price Analysis (AHSP), and price lists for scaffolding and PCH. The collected data were analyzed to calculate the time productivity and cost of each scaffolding method. The results indicate that PCH is more effective in terms of time, offering a saving of approximately 4 days or 20% compared to scaffolding. However, in terms of cost, scaffolding is more efficient, as the cost of using PCH is approximately 24% higher. Therefore, it can be concluded that PCH excels in time effectiveness, while scaffolding is more suitable for cost efficiency in the execution of this project.